A Review of Ethnographic Use of Wooden Spears and Implications for Pleistocene Hominin Hunting. (9th September 2020) - Milks, Annemieke
Wooden spears are amongst the earliest weapons known from the archaeological record, with broken and complete examples known from Middle and Late Pleistocene Eurasian, Australian and South American sites. They were manufactured and used by multiple species of Homo, including H. sapiens . This paper comprises the first systematic review of ethnographic data on the recent use of wooden spears for hunting and human violence. It confronts the historical racism underpinning the abuse of ethnographic data on wooden spears, including associations between the technology and the development of cognitive abilities in human evolution. The review demonstrates that wooden spears were used as thrusting and throwing weapons by recent societies in North America, South America, Africa, and Oceania, and continue to be used today by children as training tools in hunter-gatherer societies. Their use is recorded in a wide range of climates and environments, using a variety of different hunting strategies to target terrestrial and aquatic prey. Whilst acknowledging limitations of ethnographic datasets, Middle and early Late Pleistocene hominin hunting is reconsidered, briefly overviewing wooden spears in relation to the variety of climate and ecological settings in which Pleistocene hominins hunted, targeted prey, and the potential for delivery methods and hunting strategies. The results underscore the importance of systematic reviews when utilising ethnography in interpreting archaeological evidence: selective references in relation to the use of wooden spears have overlooked additional examples that point to a richness and variability of technology and behaviour that is invisible in the Pleistocene archaeological record.